Pengaruh Work Life Balance terhadap Work Engagement pada Ibu Bekerja - Satrio Budiman Rastanim; Lisa Widawati; Ayu Tuty Utami (UNISBA Press, 2024)
Abstract. Work engagement is motivation, positivity, fulfillment, and an individual's perspective which is characterized by vigor, dedication, and absorption (Schaufeli et al., 2002). Work life balance is the ability to achieve goals and fulfill various demands of work and life and achieve satisfaction in all aspects of life (Fisher and Bulger, 2012). The aim of this research is to determine the effect of work life balance on work engagement in working mothers. The subjects in this study were 105 working mothers. The data analysis technique used is simple linear regression. The work life balance measuring tool uses the Work Life Balance Scale by Fisher, Bulger and Smith (2009) which has been adapted into Indonesian by Gunawan et al (2019). Meanwhile, the work engagement measuring tool uses the Utrecht Work Engagement Scale-9 (UWES-9) by Schaufelli and Bakker (2003) which has been adapted into Indonesian by Kristiana et al (2018). The research results show that work life balance has an influence of 28.1% on work engagement among working mothers. Abstrak. Work engagement merupakan suatu motivasi, hal positif, pemenuhan, serta cara pandang individu yang di tandai dengan adanya vigor, dedication, dan absorption (Schaufeli et al., 2002). Work life balance merupakan kemampuan dalam mencapai tujuan dan memenuhi berbagai tuntutan pekerjaan maupun kehidupan dan mencapai suatu kepuasan dalam seluruh aspek kehidupan (Fisher dan Bulger, 2012). Tujuan dari penelitian ini untuk mengetahui pengaruh work life balance terhadap work engagement pada ibu bekerja. Subjek pada penelitian ini adalah ibu bekerja sebanyak 105 orang. Teknik analisis data yang digunakan regresi linear sederhana. Alat ukur work life balance menggunakan Work Life Balance Scale oleh Fisher, Bulger dan Smith (2009) yang sudah diadaptasi kedalam bahasa Indonesia oleh Gunawan et al (2019). Sedangkan alat ukur work engagement menggunakan Utrecht Work Engagement Scale-9 (UWES-9) oleh Schaufelli dan Bakker (2003) yang sudah diadaptasi kedalam bahassa Indonesia oleh Kristiana et al (2018). Hasil penelitian menunjukkan bahwa work life balance memberikan pengaruh sebesar 28.1% terhadap work engagement pada ibu bekerja.